Hawaiian Blood : Colonialism and the Politics of Sovereignty and Indigeneity - Kauanui, J. Kēhaulani, 1968- (Book collections on Project MUSE., 2008)
Study of the legal and cultural effects of the "fifty-percent blood quantum" rule which was first instituted in the 1920s to define who counted as a native Hawaiian and which has continuing influence on legislation and on the Hawaiian sovereignt